2015
DOI: 10.1016/j.str.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding Mechanism in Steroid Receptors: From Conserved Plasticity to Differential Evolutionary Constraints

Abstract: Steroid receptor drugs have been available for more than half a century, but details of the ligand binding mechanism have remained elusive. We solved X-ray structures of the glucocorticoid and mineralocorticoid receptors to identify a conserved plasticity at the helix 6-7 region that extends the ligand binding pocket toward the receptor surface. Since none of the endogenous ligands exploit this region, we hypothesized that it constitutes an integral part of the binding event. Extensive all-atom unbiased ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 53 publications
3
131
0
Order By: Relevance
“…In contrast, B, Aldo and DOC, which lack a 17α-hydroxyl, would not clash with Leu-848, explaining the stronger response of the MR to these steroids. However, a crystal structure of the MR with DEX (Edman et al 2015) did not find a steric clash between Leu-848 on the MR and the 17α-hydroxyl on DEX due to plasticity in helix6-helix7 in the MR, which allows for an open conformation that can accommodate DEX. A molecular mechanics (Monte Carlo simulations) and crystallographic analysis of the MR, GR, PR, ER and AR revealed that such plasticity is present in MR, GR, PR and ER, but not in the AR.…”
Section: Ser-843 In Human Mr: Role In Divergence From the Grmentioning
confidence: 97%
See 4 more Smart Citations
“…In contrast, B, Aldo and DOC, which lack a 17α-hydroxyl, would not clash with Leu-848, explaining the stronger response of the MR to these steroids. However, a crystal structure of the MR with DEX (Edman et al 2015) did not find a steric clash between Leu-848 on the MR and the 17α-hydroxyl on DEX due to plasticity in helix6-helix7 in the MR, which allows for an open conformation that can accommodate DEX. A molecular mechanics (Monte Carlo simulations) and crystallographic analysis of the MR, GR, PR, ER and AR revealed that such plasticity is present in MR, GR, PR and ER, but not in the AR.…”
Section: Ser-843 In Human Mr: Role In Divergence From the Grmentioning
confidence: 97%
“…Figure 5 also shows the α-helices on the MR as determined by X-ray crystallography (Bledsoe et al 2005, Fagart et al 2005, Edman et al 2015 and amino acids that have been found to be important in either steroid binding or transcriptional activation of the MR or CR (Fagart et al 1998, Geller et al 2000, Bledsoe et al 2005, Hultman et al 2005, Bridgham et al 2006, Shibata et al 2013, Edman et al 2015, Jimenez-Canino et al 2016, Mani et al 2016 or the GR (Bledsoe et al 2002, He et al 2014, Edman et al 2015, Mani et al 2016. A striking feature, discussed in more detail below, is the strong conservation of amino acids among the CR, MR, GR, PR and AR, including lamprey PR and CR.…”
Section: Lldsmhdlvsdllefcfytfreshalkvefpamlveiisdqlpkvesgnakplyfhrkmentioning
confidence: 97%
See 3 more Smart Citations